THE EFFECT OF BRAND IMAGE, BRAND TRUST AND PRICE ON CUSTOMER LOYALTY OF INDOMIE INSTANT NOODLE PRODUCTS FEB STUDENTS OF MALIKUSSALEH UNIVERSITY - Durrah Safira; Halida Bahri; Naufal Bachri; Rusydi Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine how brand image, brand trust and price influence customer loyalty of Indomie instant noodle products among students of the Faculty of Economics and Business, Malikussaleh University partially and simultaneously. The data used in this study are primary data obtained by distributing questionnaires to 120 respondents. The questionnaire trial consists of validity and reliability tests using the Cronbach's Alpha method. The classical assumption test uses the normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing uses the t-test, F test and coefficient of determination R2. The data analysis technique used is multiple linear regression using SPSS software version 26. The results of the study show that the Brand Image variable has a significance value of 0.007 and a t-value of 2.763> t-table, namely 1.981, which means it has a positive and significant effect on Customer Loyalty. Thus, the first hypothesis is accepted. Meanwhile, the Brand Trust variable has a significance value of 0.001 and a t-value of 3.368> t-table, which means it has a positive and significant effect on Customer Loyalty, so the second hypothesis is accepted. Furthermore, the Price variable shows a significance value of 0.001 and t count of 3.272 > t table, which means it has a positive and significant influence on Customer Loyalty, so the third hypothesis is accepted. Thus, it can be concluded that brand image, brand trust, and price partially and simultaneously have a positive and significant influence on customer loyalty.